The Relationship between Personal Factors and Online Financial Transaction Behavior of People in Nan Province - Kumprasert, Ponlawat; Pinprayong, Boriboon; Silparcha, Wanna (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purpose of this research was to study the relationship between personal factors and online financial transaction behavior of people in Nan province. A questionnaire was used to collect data from 400 people in Nan Province by simple random sampling with the districts, then quota random sampling with proportional to the number of samples, and convenient sampling. Statistics used in data analysis were frequency, percentage, mean, standard deviation, and chi-square test. The results showed that personal factors which were age, education, occupation and income had a correlation with the online financial transaction behavior on the application/website/online service used with statistically significant at the .05 level. But the study was not correlated with use of Twitter and internet banking. Age has no relation to the use of financial applications and internet banking. Gender was only associated with use of Twitter and online trading applications/websites. The personal factors with age, education, occupation and income were related to the utilization of using online applications/websites/services with a statistically significant at the .05 level. But age was not correlated with the average annual amount spent on money transfers/other financial transactions, and gender was not correlated in any respect to the utilization of online applications/websites/services. The respondents had the top 3 most concerning online transactions are information security. Attractive promotions and benefits Easy steps, easy access